Recession impact on Malay companies: case of Perak Malay Chamber of Commerce Malaysia (PMCCM) / Hasnida Abdullah, Junita Mior Shahid and Mohd Faizul Nizam Ghazali - Abdullah, Hasnida; Mior Shahid, Junita; Nizam Ghazali, Mohd Faizul (2006)
This paper focuses on the recession impact on Malay companies (profit and loss) - case of Perak Malay Chamber of Commerce Malaysia (PMCCM). As a result, the Malaysian economy experienced its deepest recession and the Gross Domestic Product (GDP) contracted by seven point five percent (7.5%) in 1998 (Mahani Zainal Abidin, 2000). As with other affected countries, Malaysia adopted the orthodox approach to such a crisis, namely tightened fiscal and monetary policies, introduce measures to redress the balance of payment weakness and floated the exchange rate. It also has risen up several complicated management disorder and financial issues to the Malays. Lower income workers and small Malay entrepreneurs facing financial difficulties towards the recession. As a result, the domestic economy continued to deteriorate, and the exchanged rate remained volatile. Companies' loss of efficiency and loss productivity due to recession. Companies facing lower domestic demand, higher interest rate thus they tend to downsizing and finally shut down their business. Lower income workers and small Malay companies dramatically facing financial difficulties towards the recession.